(untitled) ("Temas Sociais" Journal, 2024)
The subject of the present investigation is the work carried out by projects implemented by institutions belonging to the Rede Entregrades, within Portuguese prison establishments. This study aims to: 1) provide a concise characterization of these projects; 2) understand their perceptions regarding the impacts of the interventions conducted; 3) identify their main challenges. The analysis began with a review of the information available on institutional websites. However, the analysis of the available data did not yield consistent results, prompting the need for semi-structured interviews. The effects of neoliberal policies underscore the state’s relinquishment of responsibility; the task of promoting and supporting reintegration falls upon civil society and its organizations, facilitated through funded projects and substantial reliance on volunteer work, thus resulting in deprofessionalization.